ACUTE MESENTERIC ISCHEMIA: EXPERIENCE IN A TERTIARY CARE HOSPITAL - Hussain, Dildar; Sarfraz, Shahid Latif; Baliga, Suresh K; Hartung, Rolf; Facahrtz, Facahrtz (Journal of Ayub Medical College Abbottabad, 2009)
Background: Acute mesenteric ischemia is an abdominal catastrophe. This has been described as a complex of diseases rather than a single clinical entity. The incidence in United States is 1 in 1000 hospital admissions. The objective of this descriptive study was to determine the clinical presentations and out come after surgery of patients with acute mesenteric ischemia. It was conducted at Dubai Hospital, Dubai, United Arab Emirates. Methods: All patients having per operative or histopathological diagnosis of acute mesenteric ischemia from 2002 to 2006 were included. Results: There were 16 patients in all. Their mean age was 51 years, 12 were male and 4 were female. Abdominal pain was present in 16 patients, vomiting in 12 and anorexia in 9 patients. Abdominal tenderness was present in 16 patients, abdominal distension and rebound tenderness in 12 patients. Five patients had hypertension, 4 had myocardial infarction and 4 had diabetes mellitus as risk factors. X-Ray abdomen was done in 13 patients, Ultrasound in 9 and CT Scan in one patient. Resection of bowel was done in 14 patients. Post operatively 5 patients developed pneumonia, 3 had wound dehiscence, 3 had sepsis, and 3 had Lower GI bleeding. Five patients were expired after surgery in the hospital. Four patients were lost to follow up. Conclusion: We should have a high index of suspicion for mesenteric ischemia in patients with unexplained abdominal pain. Early diagnosis and prompt surgical intervention improves the outcome. Keywords: Mesenteric Ischemia, Diagnosis, Surgery Outcome